2006
DOI: 10.1590/s0004-28032006000200002
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência ambulatorial em um hospital geral de marcadores para hepatites B e C em pacientes com infecção pelo vírus da imunodeficiência humana

Abstract: RESUMO -Racional -Os vírus das hepatites B (VHB) e C (VHC) e da imunodefi ciência humana (HIV) utilizam a mesma rota de transmissão, sendo a prevalência de VHB e VHC em pacientes infectados pelo HIV maior do que aquela encontrada na população em geral. Objetivo -Determinar a prevalência de marcadores para hepatites B e C em uma população de pacientes com HIV, bem como os fatores de risco envolvidos.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 35 publications
(45 reference statements)
2
10
0
2
Order By: Relevance
“…HBV/HIV and HCV/HIV prevalences were 3.7% and 5.4% respectively. These are in accordance with other Brazilian published data, in which values ranged from 2.8%-4.6% for HBV/HIV co-infection (7,15,19) and 4%-6.4% for HCV/HIV association (6,7,17) . Similar to our study, these researches tested HIV patients who were in medical follow-up in infectious disease centers in four distinct Brazilian cities: São Paulo, Porto Alegre, Amazonas and Vitória.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…HBV/HIV and HCV/HIV prevalences were 3.7% and 5.4% respectively. These are in accordance with other Brazilian published data, in which values ranged from 2.8%-4.6% for HBV/HIV co-infection (7,15,19) and 4%-6.4% for HCV/HIV association (6,7,17) . Similar to our study, these researches tested HIV patients who were in medical follow-up in infectious disease centers in four distinct Brazilian cities: São Paulo, Porto Alegre, Amazonas and Vitória.…”
Section: Discussionsupporting
confidence: 93%
“…Other studies report the same difficulty in testing patients for hepatitis. Tovo et al found that only 58.4% (343/587) of the HIV patients on medical follow-up in a tertiary unit in south Brazil were tested for either HBV or HVC serologies (15) . Other authors, however, report successful experiences, which leaded to better results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, patients with hepatic steatosis due to the obesity, alcohol consumption or DM respond to treatment less frequently than patients without steatosis (6) and in HIV co-infected patients the virologic response frequency is lower than the patients without co-infection (17) . The epidemiological results presented by TOVO et al (18) , GALPERIM et al (8) and PAROLIN et al (14) are important for public health decision making, because they refl ect the reality found in daily clinical practice. In Brazil, where most high cost medical treatment has been defrayed by the government it is important to perform local pharmacoeconomical studies.…”
Section: Hepatitis C -Facts In Numbersmentioning
confidence: 92%
“…In the fi rst, TOVO et al (18) , describe the frequency of HBV-HIV and HCV-HIV co-infections, being important the association of HCV. Among those who tested for anti-HCV, 126/330 (38.2%) were positive, being the use of intravenous drug abuse (75.3%) the main risk factor in this group.…”
Section: Hepatitis C -Facts In Numbersmentioning
confidence: 99%